2005
DOI: 10.1542/peds.2004-2084
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Costs for Children Who Have Special Health Care Needs and Are Enrolled in a Hospital-Based Comprehensive Primary Care Clinic

Abstract: ABSTRACT. Objective. When deciding how much hospital resources should be allocated to comprehensive primary care clinics for children with multisystem disorders, it is important to consider all of the non-primary care revenue streams associated with these children as well as the effects of a comprehensive primary care program on access and quality. The objectives of this study were, first, to determine costs as well as the payments associated with hospital ambulatory and inpatient services for children with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 20 publications
(18 reference statements)
2
61
0
1
Order By: Relevance
“…As Lantos 8 described in his experience as an administrator at an academic institute, high-risk infant follow-up programs are seen as unprofitable to the hospital with poor reimbursement rates from insurance companies. This was also proved by Berman et al 9 when they reported that the hospital lost $1556 per child per year for outpatient services when children with multisystem disorders were seen in a special primary care clinic. This loss was partially offset by a gain of $598 per child in the inpatient services.…”
Section: Discussionmentioning
confidence: 65%
“…As Lantos 8 described in his experience as an administrator at an academic institute, high-risk infant follow-up programs are seen as unprofitable to the hospital with poor reimbursement rates from insurance companies. This was also proved by Berman et al 9 when they reported that the hospital lost $1556 per child per year for outpatient services when children with multisystem disorders were seen in a special primary care clinic. This loss was partially offset by a gain of $598 per child in the inpatient services.…”
Section: Discussionmentioning
confidence: 65%
“…[26][27][28] To our knowledge, this is the first study outside of the asthma population to explore relationships between early postdischarge hospital utilization and medical home experience.…”
Section: Discussionmentioning
confidence: 99%
“…8 Some of these programs have reported a major impact on health care utilization and costs, suggesting that they may help interrupt the cycle of persistent health care spending that the children would have experienced otherwise. [9][10][11][12][13] As for their adult counterparts, 14 hospital care is a significant contributor to the overall cost accrued by children with chronic conditions. 2,5,6 Many children who experience high health care costs incur frequent hospital admissions and lengthy hospitalizations.…”
mentioning
confidence: 99%